Burnout among general practitioners, a systematic quantitative review of the literature on determinants of burnout and their ecological value - Verhoef, Nicolaas Cornelis; Blomme, Robert Jan (Frontiers in Psychology, 2022)
Abstract Burnout is a major social and economic problem, specifically among GPs. The amount of literature on generic determinants of burnout is impressive. However, the size of the library on occupation-specific determinants of burnout among GPs is minimal. The present study, a systematic quantitative literature review, aims to gain insight into the existing academic literature on generic and occupation-specific determinants of burnout among GPs. Furthermore, by emphasizing occupation-specific determinants, we aim to contribute to the ecological validity of this study. An extensive literature search revealed 60 eligible studies. Following the Prisma statement, quality assessments according to the Axis, Casp, MMAT, and 3-Min procedures,30 strong studies, and 30 moderate studies were distinguished. Analyzing those studies delivered 75 determinants of burnout, of which 33 were occupation-specific for GPs. We assessed frequency effect sizes(FES) and intensity effect sizes(IES). According to the average FES, occupation-specific determinants play a significant role in acquiring burnout compared to the generic determinants. By performing a Fisher exact test, we found evidence that the quality of the 60 studies did not affect the outcomes. We conclude that it is surprising that a profession with such an important social position and such a high risk of burnout has been so little researched.